1996
DOI: 10.1002/bjs.1800830522
|View full text |Cite
|
Sign up to set email alerts
|

Aortic prosthetic infection: 50 Patients treated by radical or local surgery

Abstract: Fifty patients with aortic prosthetic infection were managed in a period of 10 years from 1983 to 1993. Twenty-five patients had recurrent sepsis after local surgery (group 1) and 22 of these eventually required radical surgery. Twenty-five patients had radical graft excision as the first procedure (group 2). Group 1 contained an excess of patients with local groin symptoms (11 in group 1 versus five in group 2, P = 0.03) and in this group fewer radiological techniques were used to document the extent of graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…However, revascularization is not possible when there is a diffuse bacterial contamination. In principle, an infected graft should always be removed and the distal blood flow restored by using an extra‐anatomic bypass (9, 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, revascularization is not possible when there is a diffuse bacterial contamination. In principle, an infected graft should always be removed and the distal blood flow restored by using an extra‐anatomic bypass (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…In vascular surgery, extra‐anatomic bypass represents the preferred method of revascularization in the case of an infected graft (9, 10), especially when major vessels are involved. Less aggressive treatments, such as partial resection of the prosthetic graft or excision and reconstruction by interposition with a vascular prosthesis, usually result in recurrence of the infection and failure to provide adequate distal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 All of these techniques have mortality rates ranging from 30% to 70% and extensive morbidity, with amputation rates approaching 30%. [13][14][15][16][17] In studies that reported results of extra-anatomic bypass for abdominal aortic graft infection, the overall patency is ϳ65% at 3 years. 14 The interval between graft implantation and the clinical manifestation of infection is variable, ranging from a few days to many years; in one group of 45 patients, the mean interval was 40.3 months.…”
Section: Betweenmentioning
confidence: 99%
“…[13][14][15][16][17] In studies that reported results of extra-anatomic bypass for abdominal aortic graft infection, the overall patency is ϳ65% at 3 years. 14 The interval between graft implantation and the clinical manifestation of infection is variable, ranging from a few days to many years; in one group of 45 patients, the mean interval was 40.3 months. 18 Organisms such as Staphylococcus aureus or Escherichia coli usually cause problems within a few weeks or months after graft insertion.…”
Section: Betweenmentioning
confidence: 99%
See 1 more Smart Citation